An investigation of the relationship between test anxiety and academic performance in secondary schools in Nyeri district, Kenya - Ndirangu, G. W; Muola, James Muthee; Kithuka, M. R; Nassiuma, D. K (Bachudo Science Ltd, 2009)
The objective of this study was to determine the relationship between test anxiety and academic performance among students in Nyeri district, Kenya. The correlational study design was used. The study was carried out among form four students together with their teachers. The target population was 83,000 students and 600 teachers from the District. Eighty students from four schools and 12 teachers were randomly sampled. Three instruments prepared by the researchers were administered, that is, a Students’ Questionnaire, a Teachers’ and a Students’ Interview Schedules. The results showed that there is a statistically significant difference (P < 0.01, t = -3.736) between test anxiety levels before and after examinations. High anxiety is experienced before the examination in all subjects. It was also established that both girls and boys are equally affected by test anxiety. The results showed that teachers do not adequately help students cope with test anxiety. There was no significant relationship (r = 0.06) between test anxiety and academic performance. It was recommended that a curriculum that is inclusive of strategies of coping with test anxiety be developed
Keywords: Test; Anxiety; Academic performance; Coping strategies; Examination